Effects of Transcranial Direct Current Stimulation (tDCS) and Exercises Treadmill on Autonomic Modulation of Hemiparetic Patients Due To Stroke—Clinic Test, Controlled, Randomized, Double-Blind - Heinz, Glauber; De Angelis, Katia; Dal Corso, Simone; Sousa, Maria Helena Gomes De; Viana, Ariane; Dos Santos, Fernando; Corrêa, João Carlos Ferrari; Corrêa, Fernanda Ishida (Frontiers in Neurology, 2020)
Background: After a Stroke, there is an autonomic nervous system (ANS) changes. Transcranial Direct Current Stimulation (tDCS) can promote the reorganization of the affected circuits. Objective: To evaluate the effects of tDCS applied before a session of physical activity on the treadmill, in the modulation of the autonomic nervous system of post-stroke patients. Methodology: Cross-over study, were randomized 12 adult hemiparetic subjects in 2 groups, Group 1 (active tDCS before exercise on the treadmill) and Group 2 (sham tDCS before exercise on the treadmill). Stimulation times were 20 minutes; treadmill time was 20 minutes. The heart rate variability (HRV) and Variability of Systolic Blood Pressure (VSBP) were evaluated for 15 minutes, in 3 periods (pre and post tDCS and during exercise recovery on the treadmill). Results: There was no difference in the VSBP and the HRV between the groups, compared with the baseline data; however, in the intragroup analysis, the parasympathetic modulation after active tDCS increased by 18% over baseline by the RMSSD with IC 95% (-7.85 - -0.34). In group 1, the post-tDCS active and post-exercise periods presented a value of variance above baseline, indicating a better prognosis. In group 2, there was a significant reduction of 38% of Variance values (p = 0.003) after tDCS sham. Conclusion: tDCS does not generate immediate effects on HRV and APV, except for intragroup comparison, which has greater participation in parasympathetic tone in the group receiving active tDCS.